2019
DOI: 10.1080/14786419.2018.1556654
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus bisporus-derived β-glucan enter macrophages and adipocytes by CD36 receptor

Abstract: β-glucans are a heterogeneous group of natural polysaccharides. They are ubiquitously found in bacterial or fungal cell walls, cereals, seaweed, and mushrooms. The beneficial role of β-glucan in tumor, insulin resistance, dyslipidemia, hypertension, and obesity is being continuously documented. Ample evidence showed that β-glucan could act on several receptors, such as Dectin, complement receptor (CR3), TLR-2, 4, 6 and scavenger. Based on the above, we wanted to explore whether agaricus bisporus-derived β-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…However, it is not clear if TLR2 is the specific β-glucan receptor because it is not normally expressed in the cells 18 . Interestingly, a recent study suggests the role of CD36, a scavenger receptor, as a β-glucan receptor in both macrophages and 3T3-L1 adipocytes 48 . Thus, future investigation is required to identify the specific β-glucan receptor on adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear if TLR2 is the specific β-glucan receptor because it is not normally expressed in the cells 18 . Interestingly, a recent study suggests the role of CD36, a scavenger receptor, as a β-glucan receptor in both macrophages and 3T3-L1 adipocytes 48 . Thus, future investigation is required to identify the specific β-glucan receptor on adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, Dectin-1 is the best characterized receptor, reported to bind β-glucan from different sources, and is expressed on the surface of monocytes, macrophages, neutrophils, DC and T lymphocytes [22]. Other PRR, including lactosylceramide receptor, mannose receptor, complement and scavenger receptors were reported to directly bind β-glucan or to cooperate with Dectin-1 for its recognition [15,21,23]. Recently, β-glucan was shown to stimulate NK cell cytotoxic activity through direct binding to the NKp30 activating receptor [24].…”
Section: Dietary β-Glucans: Main Features and Sourcesmentioning
confidence: 99%
“…Interestingly, a recent report suggested cluster of differentiation 36 (CD36), a scavenger receptor, as a candidate for a b-glucan receptor on the surface of macrophages and differentiated adipocytes 17 . CD36 plays a major role as a receptor that mediates the uptake of fatty acids in skeletal muscles and adipose tissues 41 .…”
Section: Possible B-glucan Receptors On 3t3-l1 Adipocytesmentioning
confidence: 99%
“…Interestingly, TLR2 has been suggested as a receptor candidate for b-glucan in 3T3-L1 adipocytes due to its upregulation in the cells upon the treatment with lipopolysaccharide or LPS 15,16 . In addition to TLR2, a recent study suggested the CD36, a scavenger receptor, to be a b-glucan receptor on both macrophages and 3T3-L1 adipocytes 17 . Therefore, while the structure and function of b-glucan receptors in the immune cells have been well characterized, it remains unclear for what the b-glucan receptor is on the 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%